Microstructure and mechanical properties of SiCp/AZ91 composite processed with extrusion and EPT. Issue 3 (11th February 2021) - Wu, Hongfei; Shan, Zhaohui; Fan, Jianfeng; Zhang, Qiang; Deng, Kunkun; Wu, Yucheng; Li, Weiguo; Dong, Hongbiao; Xu, Bingshe
Abstract : By hot extrusion at 250°C and electrical pulse treatment (EPT) of 40 μs duration and 10 min processing time, a homogeneous matrix microstructure with an average grain size of 0.91 μm and abundant Mg17 Al12 phase was obtained in SiCp/AZ91 magnesium matrix composite. Moreover, SiCp were helpful to promote the accumulation of crystal defects and the precipitation of Mg17 Al12 phase. After extrusion at 250°C, the yield strength (YS) and ultimate tensile strength (UTS) of the composite reached 480 and 556 MPa, respectively. With the increase of the duration and the processing time, the YS and UTS of SiCp/AZ91 composite were reduced due to the softening effect of static recrystallisation but its tensile elongation to failure (TEF) was improved slightly.